(untitled) (Baghdad Science Journal, 2021)
Pathogenic microorganisms from hospitals, communities, and the environment remain great threats to human health. The increasing concern about antibiotic resistance has also necessitated the search for robust alternatives. Therefore, this study aims to isolate, screen and evaluate the antibiotic susceptibility of Pseudomonas aeruginosa isolated from a soil sample taken from northern, western and eastern parts of Kelana Jaya Lake against four antibiotics (gentamycin, tetracycline, ampicillin, and penicillin) on a Mueller-Hinton Agar media plate. Pseudomonas identification was done by using API 20 kit. Disc diffusion was employed as well as the oxidase test. From the positive oxidase result, the isolated bacteria were identified as Burkholderia cepacia (97.6% ID), Pseudomonas aeruginosa (99.5-99.9% ID), and Pseudomonas fluorescent (75.9% ID). Only Pseudomonas aeruginosa isolates were further evaluated for antibiotic susceptibility tests. The result showed that P. aeruginosa was susceptible to only three antibiotics (gentamycin, tetracycline, and penicillin) showing a clear zone of inhibition while it was resistant to only ampicillin with no zone of inhibition. Soil isolates are potential sources for the development of effective antibiotics against resistant bacteria. Keywords: Antibiotics; Bacterial resistance; Sensitivity, Pseudomonas